SERS Based Lateral Flow Assay for Rapid and Ultrasensitive Quantification of Dual Laryngeal Squamous Cell Carcinoma-Related miRNA Biomarkers in Human Serum Using Pd-Au Core-Shell Nanorods and Catalytic Hairpin Assembly - Li, Guang; Niu, Ping; Ge, Shengjie; Cao, Dawei; Sun, Aidong (Frontiers in Molecular Biosciences, 2022)
Non-invasive early diagnosis is of great significance in disease pathologic development and subsequent medical treatments, and microRNA (miRNA) detection has attracted critical attention in early cancer screening and diagnosis. However, it poses high demand and challenge for a specific, efficient, and economic miRNA assay method due to the high homology, interference from analogue, as well as limitations in the current assay technologies. Herein, we developed a surface-enhanced Raman scatting (SERS) based lateral flow assay (LFA) biosensor, assisted with catalytic hairpin assembly (CHA) amplification strategy, which could realize the dynamic monitoring of miR-106b and miR-196b, associated with laryngeal squamous cell carcinoma (LSCC). In the presence of target miRNAs, two hairpin DNAs could self-assemble into double-stranded DNA, exposing the biotin molecules modified on the surface of Pd-Au core-shell nanorods (Pd-AuNRs) and the biotin molecules could be captured by the streptavidin (SA) which was fixed on the test lines (T1 line and T2 line) beforehand. The core-shell spatial structures and aggregation Pd-AuNRs on the T line generated abundant active “hot spots”, significantly amplifying the SERS signals. Using this strategy, the limits of detections were low to aM level and the selectivity, reproducibility and uniformity of the proposed SERS-LFA biosensor were satisfactory. Finally, this rapid analysis strategy was successfully applied to quantitatively detect the target miRNAs in clinical serum obtained from healthy subjects and LSCC patients at different stages, and the results were consistent with those of the real-time polymerase chain reaction (qRT-PCR). Thus, the CHA assisted SERS-LFA biosensor would become a promising alternative tool for miRNAs detection, which showed a great clinical application prospect in the diagnosis of LSCC.